DIGITAL TRANSFORMATION IN INDUSTRIAL MANAGEMENT: CHALLENGES AND OPPORTUNITIES - Suwanda, Suwanda (Jurnal Price : Ekonomi dan Akuntasi, 2023)
This research examines the impact of digital transformation on industrial management and investigates the challenges and opportunities that arise with the adoption of digital technology. Through a qualitative approach, this research involves literature analysis regarding industrial players who have implemented digital transformation. The research results show that digital transformation in industrial management makes a significant contribution to increasing operational efficiency, product innovation and the organization's ability to compete in the global market. Despite being faced with challenges such as changing organizational culture, data security, and a lack of technology skills, organizations that successfully implement digital transformation gain benefits in increasing production efficiency, responding more quickly to market changes, and optimizing cross-border partnerships. This research provides a deeper understanding of the importance of digital transformation as a strategy to strengthen organizational competitiveness and continuity in an ever-changing industrial era.